Growth Response and Soybean Production (Glycine max L. Merr) Variety Anjasmoro and Grobogan on Giving Dosesof Fertilizer KCl - Panataria, Lince Romauli; Sihombing, Parsaoran; Sitorus, Efbertias; Saragih, Meylin Kristina; Manurung, Agnes Imelda (PT. Riset Press International, 2024)
This Research was conducted on the BSP (Balai Seed Parent) Tanjung Selamat land on Jl. Education with an altitude of ± 25 meters above sea level. This Research uses a Split Plot Design (SPD) using 2 factors. The aim is to determine soybean plants' response to KCl fertilizer doses. The main plot is Variety (V), which consists of V1 = Anjasmoro and V2 = Grobogan. Subplots are KCl fertilizer (P), which consists of P0 = Without KCl fertilizer, P1 = 100 kg/ha KCl (9.6 g/plot), P2 = 200 kg/ha KCl (19.2 g/plot), and P3 = 400 kg/ha KCl (38.4 g/plot). The results showed that the treatment of soybean varieties significantly affected plant height, number of pods per plant, number of seeds per pod, number of seeds per plant, weight of seeds per plant, and weight of seeds per plot. Providing KCl fertilizer significantly affected plant height, number of pods per plant, number of seeds per pod, number of seeds per plant, seed weight per plant, and seed weight per plot. The interaction between Variety and KCl fertilizer dose had no significant effect on plant height, number of pods per plant, number of seeds per pod, number of seeds per plant, seed weight per plant, and seed weight per plot.